The relationship between ergonomic factors and work stress outcomes among non-executive employees in Serian Oil Palm Mill Sdn. Bhd. / Russell Reed Boniface Alin - Boniface Alin, Russell Reed (2018)
In very challenging working environment nowadays, it is very important to employee taking care of themselves and for the employer to provide their employee the comfortable workplace environment. In workplace, sometimes there are large number of tasks that exceed the capabilities of most of the work force. The workstation conditions also contributes to work stress. It is very important apply ergonomics principles in workplace so that people can perform their work without any injury. By applying ergonomics principles can reduces cost for injury, improves productivity, quality, employee engagement, an others good benefits. This study will be examine the relationship between ergonomics factors and the work stress outcomes at the Serian Palm Oil Mill Sn Bhd (SEPOM). The total number of population in SEPOM is 187. The respondents from all departments will give their respond on health, working chair, humidity, lighting, and working hours as the independent variables towards stress outcome.